2017
DOI: 10.1371/journal.pone.0184292
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 and microRNA-21 in peripheral blood B cells associated with progression of primary biliary cholangitis patients

Abstract: Recently, there is ample evidence suggesting the important role of microRNAs (miRNAs) in autoimmune diseases via modulating B cells function. Primary biliary cholangitis (PBC) is a progressive immune-mediated liver disease with unclear pathogenic mechanism. Whether the miRNA in peripheral B cells of PBC involve the mechanisms of pathology and progression is not known. The present study explores miRNA deregulation in peripheral B-cell of PBC from stage I to IV and healthy controls. Peripheral B cells were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Hence, it is not surprising that increased miR-21 expression is closely associated with the maintenance of autoreactive immunity (Stagakis et al 2011). In dominant-negative TGF-β receptor II mice, which spontaneously develop an autoimmune cholangitis similar to human PBC the T cell dysregulation is associated with upregulation of the key inflammatory miR-21 (Ando et al 2013), and in close relevance to the present study, miR-21 has showed consistent and significant down-regulation in B cells of PBC patients from stage I to stage III of PBC (Wang et al 2017). The biological significance of this finding in a presumably T-cell mediated autoimmune liver diseases and its pathophysiological connotations in AMA positive versus AMA negative patients remains elusive.…”
Section: Introductionsupporting
confidence: 82%
“…Hence, it is not surprising that increased miR-21 expression is closely associated with the maintenance of autoreactive immunity (Stagakis et al 2011). In dominant-negative TGF-β receptor II mice, which spontaneously develop an autoimmune cholangitis similar to human PBC the T cell dysregulation is associated with upregulation of the key inflammatory miR-21 (Ando et al 2013), and in close relevance to the present study, miR-21 has showed consistent and significant down-regulation in B cells of PBC patients from stage I to stage III of PBC (Wang et al 2017). The biological significance of this finding in a presumably T-cell mediated autoimmune liver diseases and its pathophysiological connotations in AMA positive versus AMA negative patients remains elusive.…”
Section: Introductionsupporting
confidence: 82%
“…Although more than 500 miRNAs were differentially expressed in patients, only hsa-miR-223-3p and hsa-miR-21-5p showed consistent downregulation from stage I to stage III suggesting that they are related to disease progression. 51 …”
Section: Biomarkers For Pbc Diagnosismentioning
confidence: 99%
“…The expression of miR-223-3p is abnormal in a variety of diseases. For example, the expression of miR-223-3p downregulated in clear cell renal cell carcinoma [28] , ossi ed broma [29] , and primary biliary cholangitis [30] , suggesting that miR-223-3p may be involved in the occurrence and development of a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%